The Way Home, or the Way to Prison? Gender Legacies and Anti-War Protest in Russia - Novitskaya, Alexandra; Johnson, Janet Elise; Sperling, Valerie; Sundstrom, Lisa McIntosh (University of Calfornia, 2025)
This article analyzes the activist rhetoric of Put′ Domoi (The Way Home)—a prominent, Russia-based public protest movement consisting primarily of women whose family members were “mobilized” into fighting in Russia’s full-scale war against Ukraine. Using a detailed framework that describes Russia’s gender-related ideologies under Putin, we analyze Put′ Domoi’s activist rhetoric focusing primarily on the first six months of their public activism (August 2023–March 2024). We examine how the activists struggled to frame their demands in a way that would afford them some protection from repression while also allowing them to challenge the regime’s open-ended military “mobilization.” We find that this movement employed a gender-compliant framework similar to that of many grassroots wives-and-mothers movements fighting authoritarian violence within and outside of Russia, but with particular Soviet roots. Over time, Put′ Domoi became increasingly frustrated with the regime’s response to their demands and increasingly critical of the war in general. This analysis helps explain why Put′ Domoi did not immediately face repression despite engaging in regular public protests critical of Russia’s war-related policies. Our case study of Put′ Domoi also sheds light on how these kinds of women’s movements navigate the complicated repressive terrain of authoritarian rule through gender-related framing tactics.